Enhancing Community Understanding and Utilization of National Health Insurance: A Socialization and Assistance Program Initiative - Sutomo, Edi; Raharja, Endra Putra; Raharja, Surya Putra; Nurinaya (Journal of Social and Community Development, 2024)
Based on field observations in Sorong Regency, the JKN program, initiated by the government to improve public health, is still not well understood by the community. The purpose of this activity is to introduce and provide information about the JKN program to the community, as well as facilitate their registration and understanding of the program. This activity is carried out through socialization and assistance, where JKN volunteer teams are trained and deployed to help the community with registration and understanding of the JKN program. Training and socialization are conducted through direct visits to the community. After the socialization and assistance activities, the community in Sorong Regency has a better understanding of the JKN program, and more people have registered as JKN participants. The socialization and assistance activities of the JKN program in Sorong Regency have helped the community understand and engage with the program. Although there are still challenges and room for improvement, these activities are crucial to ensure that the community benefits from the JKN program.